Industri Film Indonesia : Membangun Keselarasan Ekonomi Media Film dan Kualitas Konten - Euis Komalawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
As an appreciation for creative works, the Indonesian Film Festival (FFI) and the Indonesian Film Appreciation (AFI) aimed at giving an award for the best work. The interesting part was the implementation of AFI 2015 emerged several award categories such as Appreciation for the Local Government and Film Criticism Appreciation. This occurred in the midst of concerns about the development of Indonesian film industries which tend to be stagnant. Film communities tried to give fresh ideas and break the film market. This new award can certainly be seen as an effort through the film festival program in spurring the film industries with creative work of educating the nation's children, especially film as a